Painful and multiple anogenital lesions are common in men with Treponema pallidum PCR-positive primary syphilis without herpes simplex virus coinfection: a cross-sectional clinic-based study. (16th September 2015) - Towns, Janet M; Leslie, David E; Denham, Ian; Azzato, Francesca; Fairley, Christopher K; Chen, Marcus
Abstract : Background: Chancres, the hallmark of primary syphilis, are classically described as single, painless ulcers at the site of Treponema pallidum inoculation. We aimed to determine the frequency of painful or multiple anogenital lesions of primary syphilis among men, whether there was concurrent herpes simplex virus (HSV) infection and whether HIV status altered clinical presentations. Methods: This study was conducted among men with T. pallidum PCR-positive lesions, attending a clinic in Melbourne, Australia, between 2009 and 2014. Lesions were also tested with HSV PCR, and syphilis serology undertaken. Results: 183 men with T. pallidum PCR-positive primary anogenital lesions were included. 89% were men who have sex with men, and 10.9% were heterosexual. 38 men (20.8%) were HIV positive. Anal lesions were more common in HIV-positive men (34.2%) than in HIV-negative men (11.6%). Primary lesions were frequently painful (49.2%) or multiple (37.7%), and infrequently associated with HSV (2.7%). Of 37 men with both painful and multiple primary lesions, only 8% had concurrent HSV. Presentation was not significantly altered by HIV status. Conclusions: Primary syphilis lesions are often painful and/or multiple in the absence of herpes coinfection, and may be clinically misdiagnosed.